Challenges in the identification of giftedness: Issues related to psychological assessment - Almeida, Leandro S.; Araújo, Alexandra M.; Sainz-Gómez, Marta; Prieto, Maria-Dolores (Anales de Psicología / Annals of Psychology, 2016)
This paper discusses issues related to the assessment of children and youth for the identification of giftedness, and presents specific recommendations for educational measures in order to attend to the particular characteristics and needs of these students. We outline the most common difficulties related to the psychological assessment of these children, including the lack of adequate instruments for the assessment of the multiple dimensions of giftedness, as well as the shortage of training for this identification. Regarding these difficulties, we describe some assessment procedures that assure higher levels of objectivity and validity in data, reducing the possibility of false positives and false negatives in the identification of these students. In addition to psychological tests, we present the advantages of using multiple informants and the contribution of different professionals and parents for this assessment. On the other hand, as we present giftedness as a result of a developmental process, it is important to conduct students’ assessment in phases, including an initial screening phase, followed by the sound assessment of students and nurturing. Finally, we present some suggestions for the advancement in giftedness identification and assessment, as a means to support the development of research in this area.